Preparation method and application of high-dispersion small-particle-size iron phosphate

By adding cellulose additives to the iron process and carrying out oxidation reaction, a high-dispersion small-particle iron phosphate was prepared, which solved the problem of large particle size of iron phosphate and easy agglomeration, and significantly improved the grinding efficiency and electrochemical properties of lithium iron phosphate.

CN119569010APending Publication Date: 2025-03-07WANHUA CHEM GRP CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411679400.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The iron phosphate prepared by the iron process has a large particle size and is prone to agglomeration, resulting in low grinding efficiency of lithium iron phosphate and high time and energy consumption costs.

Method used

Iron phosphate was obtained by soluble in the iron source in the phosphoric acid solution and adding hydrogen peroxide during the heating process to perform an oxidation reaction, controlling the temperature and reaction time, and finally calcining. This method can promote the nucleation of iron phosphate and inhibit crystal growth, avoid particle agglomeration.

Benefits of technology

The prepared iron phosphate is flake-like, with a particle size as low as 1 micron, and there is no particle agglomeration, which significantly shortens the sand grinding time, improves the sand grinding efficiency, reduces energy consumption, and improves the electrochemical performance of lithium iron phosphate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569010A_ABST
    Figure CN119569010A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of high-dispersion small-particle-size iron phosphate. The method comprises the following steps: 1) dissolving an iron source in a phosphoric acid solution to obtain ferrous dihydrogen phosphate; 2) adding a cellulose additive into the solution obtained in the step 1), stirring and heating; 3) heating to 60-95 DEG C, adding hydrogen peroxide, carrying out oxidation reaction, and aging; and 4) filtering the solvent, washing, drying, and roasting to obtain the iron phosphate. The iron phosphate provided by the invention is in a sheet shape, no agglomeration exists between sheets, the particle size can be as low as 1 micron or below, the grinding efficiency of lithium iron phosphate can be effectively improved, and the electrochemical performance of a lithium battery positive electrode material prepared from the lithium iron phosphate can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of flaky ferric phosphate, and in particular to a preparation method and application of highly dispersed small-particle ferric phosphate. Background Art

[0002] Lithium iron phosphate (LiFePO4, LFP) has attracted much attention as a cathode material for lithium-ion batteries. It has superior electrochemical properties and good kinetic characteristics, and can effectively carry out lithium intercalation and deintercalation processes, ensuring that the battery has stable charge and discharge performance and long cycle life. In addition, lithium iron phosphate does not contain rare or toxic metals, is environmentally friendly, has relatively low cost, and is relatively safe, and is considered to be the first choice for lithium-ion battery cathode materials.

[0003] Iron phosphate (FePO4, FP) material is the main precursor of lithium iron phosphate at present. Its morphology, specific surface area, iron-phosphorus ratio, particle size, etc. have an important influence on lithium iron phosphate. The synthesis methods of iron phosphate mainly include hydrothermal method, sol-gel method, co-precipitation method, etc. Among them, co-precipitation method is the most commonly used method for preparing iron phosphate in industrial production. According to the different raw materials, the co-precipitation method can be further divided into iron method, ammonium method and sodium method and other process routes. The ammonium method and sodium method use ferrous sulfate as raw material, with low raw material cost. They are the mainstream process routes in the current market and occupy most of the production capacity of iron phosphate. However, a large number of miscellaneous elements will be introduced in the two process routes, thereby introducing impurities into iron phosphate and increasing the cost of three waste treatment. In contrast, the iron method uses pure iron as the iron source, does not actively introduce additional impurities, has high atomic utilization efficiency, and has greater environmental advantages. In addition, the iron phosphate produced by the iron process is flaky in morphology and has a relatively high iron-phosphorus ratio. The physical properties of the product are significantly different from those of the ammonium and sodium processes. The use of iron-based iron phosphate is an important means to achieve differentiation of lithium iron phosphate. However, the iron phosphate prepared by the conventional iron process has low grinding efficiency, which greatly increases time and energy costs.

[0004] Patent CN118387849A discloses a method for preparing flaky high iron-phosphorus ratio iron phosphate, which improves the uniformity of iron phosphate particle size and improves the ball milling time for preparing lithium iron phosphate. This method first prepares seed crystals through an oxidation reaction, further adds seed crystals and oxidizes again to prepare iron phosphate. The process is complicated and still has the disadvantages of large particle size and easy agglomeration.

[0005] Therefore, a solution is needed to solve the shortcomings of the iron-based process, that is, the iron phosphate particles are large and easy to agglomerate, so as to effectively reduce the time and energy consumption in the process of preparing lithium iron phosphate. Summary of the invention

[0006] In order to solve the above technical problems, the present invention proposes a method for preparing highly dispersed small-particle iron phosphate and its application. The iron phosphate prepared by the method provided by the present invention has a flaky morphology, and there is no agglomeration between the flakes. The particle size can be as low as 1 micron or less, which can effectively improve the grinding efficiency of lithium iron phosphate. Moreover, the lithium iron phosphate prepared from the iron phosphate has the advantages of good processing performance and high electrochemical performance.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing highly dispersed small-particle ferric phosphate comprises the following steps:

[0009] 1) dissolving an iron source in a phosphoric acid solution to obtain ferrous dihydrogen phosphate;

[0010] 2) adding a cellulose additive to the solution obtained in step 1), stirring and heating;

[0011] 3) After heating to 60-95° C., preferably 65-85° C., adding hydrogen peroxide to carry out oxidation reaction and aging;

[0012] 4) After filtering out the solvent, washing, drying and roasting are carried out to obtain iron phosphate.

[0013] As some preferred examples of the present invention, in step 1), the iron source is one or more of reduced iron powder, iron block, iron sheet, ferroferric oxide, and ferrous oxide with a molar purity of metallic Fe greater than 99%.

[0014] As some preferred examples of the present invention, the usage ratio of the iron source and the phosphoric acid solution in step 1) is 1:(2-3.5) in terms of the molar ratio of metal Fe to phosphoric acid;

[0015] Preferably, the mass concentration of the phosphoric acid solution is 15-40%.

[0016] As some preferred examples of the present invention, the cellulose additive is selected from one or more of methyl cellulose, carboxymethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose;

[0017] Preferably, the cellulose additive is added to the solution obtained in step 1) at a mass fraction of 0.1-5%.

[0018] As some preferred examples of the present invention, the stirring speed in step 2) is 100-500 rpm.

[0019] As some preferred examples of the present invention, the amount of hydrogen peroxide added in step 3) is 0.5-0.75 times the molar amount of metal Fe in the iron source;

[0020] Preferably, the mass concentration of the hydrogen peroxide is 20-35%.

[0021] As some preferred examples of the present invention, the oxidation reaction time in step 3) is 20-60 min;

[0022] Preferably, the aging in step 3) is carried out at 70-95° C. for 60-120 min.

[0023] As some preferred examples of the present invention, the calcination conditions in step 4) are: calcination at 500-650° C. for 3-6 hours.

[0024] The present invention also provides a highly dispersed small-particle iron phosphate prepared according to the method described above, wherein the particle size D of the iron phosphate is 50 <5 microns, preferably D 50 <2 microns, more preferably D 50 <1.5 microns.

[0025] The present invention also provides a use of the highly dispersed small-particle iron phosphate prepared according to the method described above in the preparation of lithium iron phosphate.

[0026] In the process of preparing ferric phosphate by the iron method of the present invention, a cellulose additive is first added and then hydrogen peroxide is added to carry out an oxidation reaction, and the hydrophobic main chain of the additive can be hydrogen-bonded with the surrounding water molecules, which can increase the fluid volume and reduce the space for free movement of particles, thereby promoting a large number of nucleations of ferric phosphate and inhibiting crystal growth, and there is no inter-particle agglomeration phenomenon. In addition, the additive only contains C, H, and O elements, which can be removed after roasting in air, and no additional impurities will be introduced. The morphology of the ferric phosphate prepared by the method of the present invention is flaky, and the particle size can be as low as less than 1 micron, without particle agglomeration, greatly shortening the sanding time, improving the sanding efficiency and reducing energy consumption, and making lithium iron phosphate have higher electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is an electron microscope morphology image of the iron phosphate provided in Example 1.

[0028] Figure 2 This is an electron microscope morphology image of the iron phosphate provided for Comparative Example 1.

[0029] Figure 3 This is an electron microscope morphology image of the iron phosphate provided for Comparative Example 2.

[0030] Figure 4 This is the efficiency curve of preparing lithium iron phosphate by sand grinding iron phosphate in Example 1.

[0031] Figure 5 This is the efficiency curve of preparing lithium iron phosphate by sand grinding iron phosphate in Comparative Example 1. DETAILED DESCRIPTION

[0032] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0033] Unless otherwise specified, the raw materials and reagents in the following examples of the present invention can be purchased through conventional commercial channels.

[0034] [Example 1]

[0035] A method for preparing highly dispersed small-particle ferric phosphate comprises the following steps:

[0036] 1) Dissolve 500g of reduced iron powder in 35% phosphoric acid solution to obtain ferrous dihydrogen phosphate; the raw material is added in an amount according to a molar ratio of metal Fe to phosphoric acid of 1:3;

[0037] 2) adding methyl cellulose at a mass fraction of 1% to the solution obtained in step 1), adjusting the stirring speed to 300 rpm, and heating;

[0038] 3) After the temperature is raised to 70°C, 607.2 g of 27.5% hydrogen peroxide is added dropwise to carry out oxidation reaction. The addition and reaction time is about 30 min. Then the temperature is raised to 80°C for aging and the reaction is continued for 120 min.

[0039] 4) After filtering off the solvent, washing, drying, and calcining at 550° C. for 6 h, iron phosphate is obtained.

[0040] [Example 2]

[0041] A method for preparing highly dispersed small-particle ferric phosphate comprises the following steps:

[0042] 1) Dissolve 500g of iron sheet in 25% phosphoric acid solution to obtain ferrous dihydrogen phosphate; the raw material is added in an amount according to a molar ratio of metal Fe to phosphoric acid of 1:2.5;

[0043] 2) adding carboxymethyl cellulose to the solution obtained in step 1) at a mass fraction of 3.5%, adjusting the stirring speed to 400 rpm, and heating;

[0044] 3) After the temperature is raised to 65°C, 65.79 g of 30% hydrogen peroxide is added dropwise to carry out oxidation reaction. The addition and reaction time are about 50 min. Then the temperature is raised to 75°C for aging and the reaction is continued for 90 min.

[0045] 4) After filtering off the solvent, washing, drying and calcining at 625° C. for 4 h to obtain iron phosphate.

[0046] [Example 3]

[0047] A method for preparing highly dispersed small-particle ferric phosphate comprises the following steps:

[0048] 1) Dissolve 400g of reduced iron powder and 143g of ferric oxide in 15% phosphoric acid solution to obtain ferrous dihydrogen phosphate; the raw materials are added in an amount according to a molar ratio of metallic Fe to phosphoric acid of 1:2;

[0049] 2) adding hydroxypropyl cellulose at a mass fraction of 0.1% to the solution obtained in step 1), adjusting the stirring speed to 100 rpm, and heating;

[0050] 3) After the temperature is raised to 95°C, 91.09 g of 25% hydrogen peroxide is added dropwise to carry out oxidation reaction. The addition and reaction time is about 20 min. Then the temperature is raised to 95°C for aging and the reaction is continued for 60 min.

[0051] 4) After filtering off the solvent, washing, drying, and calcining at 575° C. for 3 h, iron phosphate is obtained.

[0052] [Example 4]

[0053] A method for preparing highly dispersed small-particle ferric phosphate comprises the following steps:

[0054] 1) Dissolve 500g of iron block in 40% phosphoric acid solution to obtain ferrous dihydrogen phosphate; the raw material is added according to the molar ratio of metal Fe to phosphoric acid of 1:2.8;

[0055] 2) adding hydroxypropyl methylcellulose at a mass fraction of 5% to the solution obtained in step 1), adjusting the stirring speed to 500 rpm, and heating;

[0056] 3) After the temperature is raised to 60°C, 52.05 g of 35% hydrogen peroxide is added dropwise to carry out oxidation reaction. The addition and reaction time are about 60 min. Then the temperature is raised to 70°C for aging and the reaction is continued for 100 min.

[0057] 4) After filtering off the solvent, washing, drying, and calcining at 600° C. for 5 h, iron phosphate is obtained.

[0058] [Example 5]

[0059] A method for preparing highly dispersed small-particle ferric phosphate comprises the following steps:

[0060] 1) Dissolve 300g of reduced iron powder and 276g of ferroferric oxide in 30% phosphoric acid solution to obtain ferrous dihydrogen phosphate; the raw materials are added in an amount according to a molar ratio of metal Fe to phosphoric acid of 1:3.5;

[0061] 2) adding carboxymethyl cellulose and hydroxypropyl cellulose to the solution obtained in step 1) at a mass fraction of 0.8% and 1.5%, respectively, adjusting the stirring speed to 200 rpm, and heating;

[0062] 3) After the temperature is raised to 85°C, 75.91 g of 20% hydrogen peroxide is added dropwise to carry out oxidation reaction. The addition and reaction time is about 40 min. Then the temperature is raised to 90°C for aging and the reaction is continued for 80 min.

[0063] 4) After filtering off the solvent, washing, drying, and calcining at 650° C. for 5.5 h, iron phosphate was obtained.

[0064] [Comparative Example 1]

[0065] Ferric phosphate was prepared in substantially the same manner as in Example 1, except that methyl cellulose was not added in step 2).

[0066] [Comparative Example 2]

[0067] Ferric phosphate was prepared in a method substantially the same as that in Example 1, except that the reaction temperature in step 3) was adjusted to 100°C.

[0068] The particle size analysis of the iron phosphate prepared in Examples 1-5 and Comparative Examples 1-2 is performed, and the results are shown in Table 1.

[0069] Table 1. Particle size analysis results

[0070] <![CDATA[D 50 / μm]]> Example 1 0.9 Example 2 1.2 Example 3 1.0 Example 4 0.9 Example 5 1.4 Comparative Example 1 9.9 Comparative Example 2 14.2

[0071] In addition, the iron phosphate provided in Example 1 and Comparative Examples 1-2 was analyzed by scanning electron microscope, and the results were as follows: Figure 1-3 As shown. It can be seen that Figure 1 The iron phosphate is in a flake-like morphology, without agglomeration, and has good dispersion; Figure 2 Although the medium iron phosphate also has a flake morphology, the flakes are seriously stacked and the dispersion of the flakes is poor; Figure 3 The iron phosphate has a flake morphology, but the colloid is denatured due to the high temperature, the growth rate of the iron phosphate crystals increases, and the nucleation rate decreases, resulting in an increase in the size of the flakes. In addition, due to the excessive growth of the iron phosphate flakes, the flakes cross each other, resulting in poor dispersion of the flakes.

[0072]

Application Example 1

[0073] The iron phosphate prepared in Example 1 and Comparative Example 1 was used as raw material, respectively, and lithium iron phosphate was prepared by sand grinding according to the following method:

[0074] 1000g of ferric phosphate was mixed with 501.2g of lithium carbonate, 8g of titanium dioxide, and 160g of glucose and placed in a sand mill. The sand mill speed was adjusted to 2000 rpm, and the data was recorded and a curve of the change of solid particle size over time was plotted. It can be seen that the ferric phosphate provided in Example 1 can be used for sand milling to achieve the particle size requirement of D50 of 450 nanometers within 15 minutes ( Figure 4), while the iron phosphate provided in Comparative Example 1 was used for sand grinding, and the particle size requirement of D50 of 450 nanometers was reached at 120 minutes ( Figure 5 ), it can be seen that the iron phosphate prepared by the present invention has a significant improvement in sand grinding efficiency. Then, it is calcined at 750°C for 10 hours in a nitrogen atmosphere, cooled to room temperature, and crushed through a 200-mesh sieve to obtain lithium iron phosphate.

[0075]

Application Example 2

[0076] The lithium iron phosphate prepared by sand grinding of iron phosphate in Example 1 and Comparative Example 1 was used as raw material to prepare the positive electrode material of lithium battery according to the following method:

[0077] The prepared lithium iron phosphate was used as the positive electrode material, mixed with a cyclohexane solution of carbon black and polyvinylidene fluoride (PVDF) at room temperature and pressure to form a slurry (according to the effective material mass ratio of positive electrode material: carbon black: PVDF = 85:10:5), and evenly coated on an aluminum foil substrate as the positive electrode of a simulated battery; a lithium sheet was used as the negative electrode of the simulated battery, and the electrolyte was 1 mol LiPF6 dissolved in a mixed solvent of 1L EC and DMC (volume ratio 1:1); the diaphragm was a composite film of polypropylene and polyethylene; the positive electrode, negative electrode, electrolyte and diaphragm were assembled into a simulated battery in an argon-protected glove box and the performance of the simulated battery was tested.

[0078] <1C discharge capacity>

[0079] First, charge to 4.2V at 30mA / g, then discharge to 2.5V at 1C current. The released capacity is the 1C discharge capacity.

[0080] <Powder compaction>

[0081] The compaction density of lithium iron phosphate powder was tested under 30kN conditions.

[0082] Table 2. Battery performance test results

[0083] 1C discharge capacity / mAh / g <![CDATA[Powder Compaction Density / g / cm 3 > Example 1 152 2.42 Comparative Example 1 146 2.35

[0084] It can be seen from the performance test results in Table 2 that the lithium iron phosphate obtained by sand grinding of iron phosphate with different morphologies has different battery performance. The iron phosphate prepared by the method of the present invention has a highly dispersed, small-particle-size flake morphology, which can not only improve the sand grinding efficiency of lithium iron phosphate, but also the obtained lithium iron phosphate has significantly improved discharge capacity and compaction density when used as a positive electrode material for lithium-ion batteries.

[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing highly dispersed small-particle ferric phosphate, characterized in that: The following steps are involved: 1) dissolving an iron source in a phosphoric acid solution to obtain ferrous dihydrogen phosphate; 2) adding a cellulose additive to the solution obtained in step 1), stirring and heating; 3) After heating to 60-95° C., preferably 65-85° C., adding hydrogen peroxide to carry out oxidation reaction and aging; 4) After filtering out the solvent, washing, drying and roasting are carried out to obtain iron phosphate.

2. The method for preparing highly dispersed small-particle ferric phosphate according to claim 1, characterized in that: In step 1), the iron source is one or more of reduced iron powder, iron block, iron sheet, ferroferric oxide and ferrous oxide with a molar purity of metallic Fe greater than 99%.

3. The method for preparing highly dispersed small-particle ferric phosphate according to claim 1 or 2, characterized in that: The ratio of the iron source to the phosphoric acid solution in step 1) is 1:(2-3.5) in terms of the molar ratio of metal Fe to phosphoric acid; Preferably, the mass concentration of the phosphoric acid solution is 15-40%.

4. The method for preparing highly dispersed small-particle ferric phosphate according to claim 1, characterized in that: The cellulose additive is selected from one or more of methyl cellulose, carboxymethyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose; Preferably, the cellulose additive is added to the solution obtained in step 1) at a mass fraction of 0.1-5%.

5. The method for preparing highly dispersed small-particle ferric phosphate according to any one of claims 1 to 4, characterized in that: In step 2), the stirring speed is 100-500 rpm.

6. The method for preparing highly dispersed small-particle ferric phosphate according to any one of claims 1 to 5, characterized in that: The amount of hydrogen peroxide added in step 3) is 0.5-0.75 times the molar amount of metal Fe in the iron source; Preferably, the mass concentration of the hydrogen peroxide is 20-35%.

7. The method for preparing highly dispersed small-particle ferric phosphate according to any one of claims 1 to 6, characterized in that: The oxidation reaction time in step 3) is 20-60min; Preferably, the aging in step 3) is carried out at 70-95° C. for 60-120 min.

8. The method for preparing highly dispersed small-particle ferric phosphate according to any one of claims 1 to 7, characterized in that: The calcination conditions in step 4) are: calcination at 500-650°C for 3-6h.

9. A highly dispersed small-particle iron phosphate prepared by the method according to any one of claims 1 to 8, characterized in that: Particle size of iron phosphate D 50 <5 microns, preferably D 50 <2 microns, more preferably D 50 <1.5 microns.

10. Use of highly dispersed small-particle iron phosphate prepared by the method according to any one of claims 1 to 8 in the preparation of lithium iron phosphate.

Citation Information

Cited By

  • Anhydrous iron phosphate as well as preparation method and application thereof

    CN120736490A

  • Anhydrous ferric phosphate, its preparation method and application

    CN120736490B

  • Preparation method of lithium iron phosphate positive electrode with bio-based cellulose as carbon source

    CN122403408A